Feasibility studies for offshore application of cross axis wind turbine / Ahmad Aiman Ezreen Abu Bakar - Ahmad Aiman Ezreen, Abu Bakar (2018)
Situation such as low wind speed on the onshore has lead to the combination of Horizontal Axis Wind Turbine (HAWT) and Vertical Axis Wind Turbine (VAWT) to tackle the high turbulence and frequent wind direction as mentioned problem by introducing the Cross-Axis Wind Turbine (CAWT). Due to abundance of high speed wind at offshore, the CAWT foundation design was simulated using Computational Fluid Dynamics to shows the performance of CAWT at site. Monopiles was chosen as design of CAWT to analyze the behavior of CAWT. The design was based on code and conduct of practice either from Malaysia or International and as reference of the design. After the simulation was completed, the techno economics of CAWT at offshore was made and the result of investigation has found it is beneficial to be constructed. This CAWT is applicable in extensive range of services and creating significant opportunities to the country for the usage of wind energy and less dependent to the depleting fossil fuel. 16 MW can be extracted through CAWT application and 5 years of payback period if operational. Keywords: Cross Axis Wind Turbine, Techno Economic, Offshore, Renewable Energy